Pengaruh Pengembangan Karir, Penempatan Kerja, Dan Pelatihan Kerja Terhadap Kinerja Karyawan Di PT Perkebunan Nusantara 1 Regional 3 Semarang - Agustin, Syifa Aulia; Wahyuni, Ana (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
This study aims to analyze the effect of career development, job placement, and job training on employee performance at PT Perkebunan Nusantara 1 Regional 3 Semarang. The research employed a quantitative approach with a causal design, using questionnaires distributed to all employees as a census sample. Data analysis techniques included multiple linear regression, validity and reliability testing, and classical assumption tests. The findings reveal that career development, job placement, and job training each have a positive and significant effect on employee performance. Simultaneously, these three variables significantly contribute to improving performance, as indicated by the significance values in both t-tests and F-tests being below 0.05, and the coefficient of determination (R²) showing substantial explanatory power. The study concludes that human resource development strategies through career advancement, proper job placement, and effective training can significantly enhance employee performance. The practical implication suggests that company management should continue optimizing these aspects to improve organizational productivity.